Navigating Human Resource Turbulence in Mergers and acquisitions: Insights from Nepal’s Banking Sectors - Upadhyaya, Prashant (International Research Journal of MMC, 2025)
Mergers and acquisitions (M&As) are increasingly adopted by banks worldwide to achieve financial consolidation, enhance competitiveness, and attain economies of scale. Despite robust financial rationale, many M&As ultimately fail due to the neglect of human resource (HR) aspects that surface during post-merger integration. This study investigates HR turbulence in Nepalese bank mergers through a mixed-methods design that combines rich qualitative insights and in-depth quantitative analyses. Semi-structured interviews (n = 43) with Branch Managers, Executives, Zoom participants, and Frontline/HR employees were subjected to thematic analysis using NVivo 12, yielding primary themes such as job insecurity, communication breakdowns, cultural incompatibility, leadership instability, and post-merger skill gaps. Concurrently, a structured survey (n = 150) administered to bank employees captured quantitative measures on key dimensions (job security, communication clarity, training adequacy, cultural compatibility, and leadership clarity) using a 5-point Likert scale. Statistical analyses in Excel—comprising descriptive statistics, graphical visualizations, and multiple regression analysis—validated three core hypotheses. Specifically, higher job insecurity was significantly associated with reduced employee morale (β = –0.65, p < .01), whereas enhanced communication clarity (β = +0.32, p < .05) and structured training programs (β = +0.43, p < .05) positively influenced morale. Overall, the regression model explained 62% of the variance in employee morale (R² = 0.62). The findings underscore the need for a proactive, people-centric integration strategy to mitigate HR turbulence in bank mergers. Recommendations for policymakers and industry practitioners are provided.